2023
DOI: 10.1007/s11356-023-25669-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microorganisms on degradation of fluopyram and tebuconazole in laboratory and field studies

Abstract: Nowadays, chemical pesticides are the most widespread measure used to control crop pests and diseases. However, their negative side effects prompted the researchers to search for alternative options that were safer for the environment and people. Pesticide biodegradation by microorganisms seems to be the most reasonable alternative. The aim of the laboratory studies was to assess the influence of Bacillus subtilis and Trichoderma harzianum, used separately and combined together, on fluopyram and tebuconazole d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Among other species, they analyzed 13 strains of Bacillus, and found only three capable of degrading Tebuconazole. Other reports [ 74 ] have shown that on the contrary, the growth of B. subtilis is inhibited by Tebuconazole; these results are similar to our observations.…”
Section: Resultssupporting
confidence: 93%
“…Among other species, they analyzed 13 strains of Bacillus, and found only three capable of degrading Tebuconazole. Other reports [ 74 ] have shown that on the contrary, the growth of B. subtilis is inhibited by Tebuconazole; these results are similar to our observations.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, certain microorganisms possess the ability to degrade the fungicides applied to plants and can weaken the protection effects provided by these agrochemicals. 64 Thus, clarification of the interplay between biocontrol microorganisms and fungicides is of considerable significance. In the present study, findings were made that the presence of T. harzianum T-22 could increase the inhibitory effect of carboxylic acid amide fungicides on P. capsici, indicating that fungicide degradation should not be a concern when combining T. harzianum T-22 and mandipropamid/dimethomorph in agricultural systems.…”
Section: Discussionmentioning
confidence: 99%